Electrochemically-mediated amine regeneration of CO2 capture: From electrochemical mechanism to bench-scale visualization study. (15th November 2021) - Wu, Xiaomei; Fan, Huifeng; Sharif, Maimoona; Yu, Yunsong; Wei, Keming; Zhang, Zaoxiao; Liu, Guangxin
Highlights: A home-designed bench-scale modular flowing-through electrolysis cells is proposed. The MFTECs enables higher electrode active surface area and lower cell resistance. An H-cell is used to study the unknown electrochemical behaviors. A visualization study of the CO2 desorption process in MFTECs was conducted. An impressive increase of desorption current to 5 A can be achieved. Abstract: Electrochemically-mediated amine regeneration (EMAR) is a new CO2 capture technology with the potential to exploit the excellent removal efficiencies of thermal amine scrubbers while reducing parasitic energy losses and capital costs. To achieve higher efficiency and explore the industrial application of the promising EMAR system, a home-designed bench-scale modular flowing-through electrolysis cells (MFTECs) is proposed. The MFTECs with MEA solvent is carefully analyzed from electrochemical mechanism to bench-scale demonstration. Firstly, a series of electrochemical experiments were conducted in an H-cell to study the unknown electrochemical behaviors under various complex concentrations and temperatures, which provided a guidance to enhance the electrochemical performance. Subsequently, a visualization study of the CO2 desorption process in MFTECs was conducted at different operating conditions (current, complex concentration, electrode position, and reaction time) to investigate the desorption performance of the proposed MFTECs system. This framework allowed for direct observation and comprehension of the CO2 desorption process, as well as the movement and interaction of CO2 bubbles in MFTECs. Finally, results indicated that the proposed MFTECs enables higher electrode active surface area and lower cell resistance. This will contribute to enhancing the regeneration performance and promoting industrial application of CO2 desorption based on EMAR.